Simulation in NS-2 of DNP3 protocol encapsulated over TCP/IP in smart grid applications - Ortega, Alcides [UNESP]; Shinoda, Ailton Akira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In dealing with computer networks, these allow the flow of information through the resources of various equipment's. This work describes the implementation through the encapsulation of Protocol DNP3, usually employed in Smart Grid communication, in a simulator of discrete events. The NS-2 is a simulator in open source of network events, that facilitate the development of communication networks scenarios considering the protocols involved, in wireless or wired technologies. The objective of this work is to develop the DNP3 protocol encapsulation over a TCP/IP in the in the discrete event Simulator NS-2, allowing an analysis of behavior of a middle or large network sized in Smart Grid applications. © 2013 IEEE.
Keywords: IEC standards; Protocols; Simulation; Smart Grids; TCPIP; Discrete events; Discrete-event simulators; Smart grid; Smart grid applications; Smart Grid Communications; Internet protocols; Network protocols; Standards; Telecommunication networks; Smart power grids